Ambit fields: a stochastic modelling approach. Issue 4 (4th July 2018) - Schmiegel, Jürgen
ABSTRACT: This paper reviews some recent developments in the field of ambit stochastics with focus on modelling applications. The great flexibility and mathematical tractability of ambit fields is illustrated by a wide range of applications, covering such diverse areas as turbulence, tumour growth and finance.